Socio-Economic Culture and Tourism: A Case Study on Saint Martin Island of Bangladesh - Tasmina Chowdhury Tania (Jurnal Aplikasi Manajemen, Ekonomi dan Bisnis, 2022)
Tourism is relevant for sustainable development and environment rehabilitation in areas with cultural value. The present condition of tourism industry and the role of tourism in the socio-economic development of Bangladesh are also very meager. In the study, questionnaire survey and other kinds of methods are used to find out the real impacts and delinquent of tourism sector based on socio-economic culture, particularly in Saint Martin’s Island. The locality of the island can protect the biodiversity by increasing the literacy rate and natural awareness. Though tourism facilities are now a bit better than the previous years, the pace of development facilities is not up to mark considering sustainable tourism. Still there is time to save the biodiversity and thereby improve the sector; otherwise it will be too late.